Preterm Birth Alters the Maturation of the GABAergic System in the Human Prefrontal Cortex - Lacaille, Helene; Vacher, Claire-Marie; Penn, Anna A. (Frontiers in Molecular Neuroscience, 2022)
Developmental changes in GABAergic and glutamatergic systems during frontal lobe development have been hypothesized to play a key role in neurodevelopmental disorders seen in children born very preterm or at/with low birth weight, but the associated cellular changes have not yet been identified. Here we studied the molecular development of the GABAergic system specifically in the dorsolateral prefrontal cortex, a region that has been implicated in neurodevelopmental and psychiatric disorders. The maturation state of the GABAergic system in this region was assessed in human post-mortem brain samples, from term infants ranging in age from 0 to 8 months (n = 17 male, 9 female). Gene expression was measured for 47 GABAergic genes and used to calculate a maturation index. This maturation index was significantly more dynamic in male than female infants. To evaluate the impact of premature birth on the GABAergic system development, samples from 1-month-old term (n = 9 male, 4 female) and 1-month corrected-age very preterm (n = 8 male, 6 female) infants, were compared using the same gene list and methodology. The maturation index for the GABAergic system was significantly lower (−50%, p < 0.05) in male preterm infants, with major alterations in genes linked to GABAergic function in astrocytes, suggesting astrocytic GABAergic developmental changes as a new cellular mechanism underlying preterm brain injury.